The Biogeographic Importance of Buoyancy in Macroalgae: A Case Study of the Southern Bull‐Kelp Genus Durvillaea (Phaeophyceae), Including Descriptions of Two New Species1. Issue 1 (21st November 2019) - Fraser, Ceridwen I.; Velásquez, Marcel; Nelson, Wendy A.; Macaya, Erasmo C.; Hay, Cameron H.
Abstract : Long‐distance dispersal plays a key role in evolution, facilitating allopatric divergence, range expansions, and species movement in response to environmental change. Even species that seem poorly suited to dispersal can sometimes travel long distances, for example via hitchhiking with other, more intrinsically dispersive species. In marine macroalgae, buoyancy can enable adults—and diverse hitchhikers—to drift long distances, but the evolution and role of this trait are poorly understood. The southern bull‐kelp genus Durvillaea includes several non‐buoyant and buoyant species, including some that have only recently been recognized. In revising the genus, we not only provide updated identification tools and describe two new species ( D. incurvata comb. nov. from Chile and D. fenestrata sp. nov. from the Antipodes Islands), but also carry out biogeographic analyses to determine the evolutionary history of buoyancy in the genus. Although the ancestral state was resolved as non‐buoyant, the distribution of species suggests that this trait has been both gained and lost, possibly more than once. We conclude that although buoyancy is a trait that can be useful for dispersal (creating evolutionary pressure for its gain), there is also evolutionary pressure for its loss as it restricts species to narrow environmental ranges (i.e., shallow depths).